Matrix Methods in the Design Analysis of Mechanisms and Multibody Systems - 440074 Uicker, John Joseph; Sheth, Pradip N., author; Ravani, Bahram, 1953- (Cambridge : Cambridge University Press, 2013)
Includes bibliographical references and index